CWTS certified wireless technology specialist study guide : - Carpenter, Tom (McGraw-Hill, 2010)
Written by a wireless networking expert and instructor, this study guide offers complete coverage of all objectives for the brand-new Certified Wireless Technology Specialist exam. CWTS certification is an ideal entry point for IT professionals intersted in enterprise WLAN certification, and targets both WLAN sales and support staff for the enterprise WLAN industry.